Effect of Sintering Time on Crystal and Structure of Chlorine-containing Low-titanium Slag Glass-ceramics. Issue 1 (December 2020) - You, Hao; Sun, Hongjuan; Peng, Tongjiang; Li, Yao; Zeng, Li; Qin, Yating
Abstract: Glass-ceramics with akermanite, diopside, spinel and perovskite crystalline phases were prepared by using the direct sintering method and using chlorine-containing low-titanium slag as a raw material. The changes in crystalline phase composition, relative content and microstructure of glass-ceramics sintered at different times were studied. The results suggested crystalline phases remained steady while the relative content of each phase changed significantly. The relative content of akermanite decreased firstly and then increased while those of diopside changed oppositely. The relative content of spinel rose from 6.6% to 9.3% and perovskite stabilized at 10.0-11.1%. In addition, the pore size of glass-ceramics declined firstly and then increased. The optimal microstrure of glass-ceramics were obtained when crystallized at 890 °C for 60 min and sintered at 1185 °C for 60 min. In general, glass-ceramics with compact microstructures could be obtained at appropriate sintering times.